Inter-stride variability triggers gait transitions in mammals and birds. Issue 1893 (19th December 2018) - Granatosky, Michael C.; Bryce, Caleb M.; Hanna, Jandy; Fitzsimons, Aidan; Laird, Myra F.; Stilson, Kelsey; Wall, Christine E.; Ross, Callum F.
Abstract : Speed-related gait transitions occur in many animals, but it remains unclear what factors trigger gait changes. While the most widely accepted function of gait transitions is that they reduce locomotor costs, there is no obvious metabolic trigger signalling animals when to switch gaits. An alternative approach suggests that gait transitions serve to reduce locomotor instability. While there is evidence supporting this in humans, similar research has not been conducted in other species. This study explores energetics and stride variability during the walk–run transition in mammals and birds. Across nine species, energy savings do not predict the occurrence of a gait transition. Instead, our findings suggest that animals trigger gait transitions to maintain high locomotor rhythmicity and reduce unstable states. Metabolic efficiency is an important benefit of gait transitions, but the reduction in dynamic instability may be the proximate trigger determining when those transitions occur.